Assessment of water and energy use at process level in the U.S. beef packing industry: Case study in a typical U.S. large‐size plant. (8th November 2018) - Li, Shaobin; Ziara, Rami M. M.; Dvorak, Bruce; Subbiah, Jeyamkondan
Abstract: Food processing industries consume intensive water and energy to produce food products. However, their water and energy data are scarce and require for good measurement approaches. This study presents data collection and analysis of process‐level water and energy use in a large‐size U.S. beef packing plant through a combined use of portable and in‐line meters and theoretical calculations. The kill floor and plant cleaning are the primary water users, accounting for 28.7 and 24.0%, respectively. The refrigeration compressor system is the largest user of electricity, consuming 24.5% of plant‐wide electricity. Heating of water for plant cleaning and food safety purposes is the largest thermal energy use in summer (81%) and second‐largest in winter (49.7%), with unit heating values of 625 and 666 MJ/ton live cattle weight in the summer and winter, respectively. Twice as much thermal energy is used in the winter than summer due to space heating requirements. A regression analysis found that as outdoor temperatures increased, a slight water use increase and larger energy use decrease were observed. Practical applications: Currently available data on water and energy use in the U.S. beef packing industry are scarce, thus limiting the ability to develop new water and energy efficient technologies and policies based on an understanding of the current baseline operations. The current study conducts a detailed assessment of water and energy use at process level to enhance the understanding of the food‐energy‐water nexus in the beef processing industry, where limited data are available. Engineers can apply this case study as an example to share with their clients seeking to collect and analyze data with the goal of identifying water and energy conservation approaches. These results will inform beef processing researchers as they design novel technologies with that may result in improved water and energy efficiencies.